Knowledge and awareness about STDs among women in Bangladesh - Hossain, Mosharaf; K. C. Mani, Kulanthayan; Mohd Sidik, Sherina; Kadir Shahar, Hayati; Islam, Rafiqul (BioMed Central, 2014)
Background Knowledge and awareness concerning sexually transmitted diseases (STDs) has become the burning issue of the day. Although STDs pose serious risks to health security, there is very little literature quantifying the knowledge and awareness of these diseases and their principal socioeconomic determinants. The aim of this study is to determine the effect of different socio-economic and demographic factors on knowledge and awareness about STDs among women in Bangladesh. Methods This is a cross-sectional study using data from the Bangladesh Demographic and Health Survey (BDHS) 2011. It involves 10,996 women in six divisions of Bangladesh – Dhaka, Rajshahi, Chittagong, Barisal, Khulna and Sylhet. In this study, the percentage distribution and logistic regression model are used to identify which factors are associated with knowledge and awareness among women in Bangladesh about STDs. Results There is a significant association between geographic division (Dhaka: OR = 1.669, 95% CI = 0.89-2.10, Khulna: OR = 2.234, 95% CI = 1.2-3.2); places of residence (Rural: OR = 0.363, 95% CI = 0.20-1.08), respondent’s age (20-29 years: OR = 1.331; 95% CI = 0.98-2.31); education (Primary: OR = 2.366, 95% CI = 1.98-3.1, secondary: OR = 10.089, 95% CI = 8.98-12.77, higher: OR = 20.241, 95% CI = 18.33-22.65); listening to radio (OR = 1.189, 95% CI = 1.29-3.12) and watching TV (OR = 2.498, 95% CI = 2.22-4.09) with knowledge and awareness among women in Bangladesh about STDs. Conclusion There is a need to improve the education in Bangladesh about STDs particularly among those in the rural areas and older ages of women (30-49 years). Formal, informal and special educational knowledge and awareness programmes may be implemented to educate people concerning STDs in Rajshahi, Sylhet and Chittangong division. Campaigns and mass media can be used to increase the knowledge and awareness among the community, especially among women. Policies concerning the issue of STDs need to be improved and can be emphasized in collaboration with government agencies to ensure the success of these campaigns.